CHALLENGES ON ACCESSING FINANCE FOR MICRO-ENTERPRISES IN LATVIA - Beizitere, Ilona; Sloka, Biruta; Brence, Ieva; Jermolajeva, Elita (LLU, 2021)
Financial support of companies for their development is considered and realised by many countries worldwide, also in Latvia. Latvia has been receiving critical remarks from entrepreneurs in regard to high level of refuse for financing from the financing institution ALTUM which is the principal intermediary of EU funds and provides resources to support entrepreneurship in Latvia. Statistical data indicate that there are significant reductions of micro-enterprises during recent years. The survey data showed that ALTUM rejected 39 % of the surveyed micro-enterprises from those who had submitted applications within three years. In turn, only 6 % of micro-enterprises have received full financing from banks or leasing companies. Funders rejected applications from 9 % of micro-enterprises while another 5 % themselves withdrew funding due to unacceptable conditions. Latvia has to address serious challenges in entrepreneurship development in regions in particular with a lower economic activity. The aim of the paper is to analyse situation of microenterprises for receiving funding. Research methods: analysis of scientific publications and results of previous conducted research, analysis of data obtained in survey of enterprises on questions of financing refuse and on evaluations related to financing conditions in recent years. For a more thorough data analysis (used evaluation scale 1-5) indicators of descriptive statistics are applied: indicators of central tendency or location – arithmetic means, mode, median; indicators of variability or dispersion – range, standard deviation, standard error of mean; cross – tabulations; testing of statistical hypotheses using t-test and analysis of variance – ANOVA; correlation analysis. Research results indicate that the use of more precise requirements of financing for micro-enterprises by finance institution ALTUM could benefit in better development of entrepreneurship in regions of Latvia.
Keywords: micro-enterprises; requirements for financing; financing refuse; ALTUM; survey; Research Subject Categories::SOCIAL SCIENCES::Business and economics